2001
DOI: 10.1116/1.1415503
|View full text |Cite
|
Sign up to set email alerts
|

Technique for 25 nm x-ray nanolithography

Abstract: The image-forming limit of x-ray lithography is said to be ∼70 nm using existing devices and technologies. This article presents methods to extend the limit to 25 nm or even below. Preparatory to the study, a light source was designed to improve x-ray beam toward shorter wavelength. In addition, a simulation code has been developed to evaluate the methods. The first method is to use a mask with a larger period and pattern than deigned images. The mask forms the designed images with an enlarged period. Two-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…6 Figure 5͑a͒ shows a 2ϫ mask of 400ϫ800 nm 2 pitch for a grating pattern. Here we note the widthwise ͑aside from lengthwise͒ image formation.…”
Section: Formation Of Two-dimensional Patternmentioning
confidence: 99%
“…6 Figure 5͑a͒ shows a 2ϫ mask of 400ϫ800 nm 2 pitch for a grating pattern. Here we note the widthwise ͑aside from lengthwise͒ image formation.…”
Section: Formation Of Two-dimensional Patternmentioning
confidence: 99%
“…Patterning with sub 100-nm resolution using a single layer of deep-UV photoresist (175 nm thick) has also been demonstrated (by using Sandia’s 10x-Microstepper Extreme ultraviolet (EUV) imaging system) [33]. At even shorter X-ray wavelengths of light, photolithography was used to fabricate structures as small as 50 nm and at a limit even sub-30 nm [3436]. Researchers at ENEA Frascati Research Center in 2008 reported the fabrication of structures with less than 90 nm using EUV at 14.4 nm [37, 38].…”
Section: Fabricationmentioning
confidence: 99%
“…8,9 The spectrum used for the simulations used in this study is shown in Fig. 1, where the ''hard'' spectrum with E m Ϸ2.64 keV is shown along with the ''medium'' and ''soft'' spectra with E m ϭ2.0 and 1.4 keV, respectively.…”
Section: Diffraction At Higher Energiesmentioning
confidence: 99%